Individual Investments Biased by the Size of a Foreign Investor: An Experimental Study - Umer, Hamza; Ahmed, Kashif; Jadoon, Muhammad Naumair (Organizations and Markets in Emerging Economies, 2021)
The field of behavioral finance has actively researched behavioral elements influencing the choices of individual investors. This study also contributes to the behavioral finance and examines the effect of an increase in a foreign firm’s partial ownership in a domestic firm on the local individual investments in that domestic firm. Specifically, using a controlled lab experiment the study examines the investments of Pakistani individual investors between a purely Pakistani firm and a Pakistani firm with three different levels of Chinese ownership (portfolio, minority, majority). The experimental results show that with reference to Chinese minority ownership in a Pakistani firm, the potential investors are 47% (61%) less likely to invest in a Pakistani firm with Chinese portfolio (majority) ownership than in a purely Pakistani firm. The study uncovers an important non-monetary factor in the form of a foreign firm’s partial ownership that can significantly influence the choices of individual investors. It also makes an important contribution to the growing literature on the Chinese foreign investments specifically in Pakistan by exploring how potential individual Pakistani investors are likely to react to an increase in Chinese investments in Pakistani firms.
Keywords: behavioral finance; partial ownership; individual investments; lab experiment; China; Pakistan